Sport and leisure-time physical activity over the life course - Claudia Klostermann; Lars Lenze; Markus Lamprecht; Siegfried Nagel (Bern Open Publishing, 2023)
It is desirable to get as many people as possible to engage in long-term leisure-time physical activity (LTPA) due to the health-enhancing effects. Although the proportion of individuals who are physically active in their leisure time appears to have increased in Switzerland in the past years NO RENDERER SUPPLIED, little is known so far about the dynamic of change in LTPA trajectories over the life course. LTPA trajectories of 1,456 Swiss residents aged 35 to 76 years (random sampling) were reconstructed with the help of a retrospective telephone interview (CATI method). To address the difficulties of retrospective data collection, the article presents the careful development of the questionnaire on the basis of current evidence. The majority of the respondents (approx. 73%) show a long-term LTPA without dropout (dropout = LTPA less than once a week over one year and longer), only a minority of whom (approx. 18%) took up their LTPA after the age of 20. In addition, there is also a group with a somewhat unstable LTPA trajectory (approx. 24%) that includes at least one dropout. For members of the latter group, the longer the inactive episode lasted, the lower were their chances of entering an LTPA. While the different LTPA trajectory groups differed only slightly with regard to socioeconomic characteristics, analyses of their sport- and physical activity-related history reveal that self-organized LTPA in childhood and youth may be seen as a success factor for lifelong LTPA. The proportion of people practicing (long-term) LTPA is presumably overrepresented in the sample. This limitation should be taken into account, but analyses of possible advantageous conditions of long-term or lifelong LTPA are nevertheless possible. The results indicate a demand for more specific theories related to the causality behind the observable LTPA behavior.